Spatial biodiversity patterns in a large New Zealand braided river - Duncan Gray; Mike R. Scarsbrook; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2006)
At the catchment scale, braided rivers are recognised as physically unstable, dynamic landscapes, yet at finer spatial scales they are a mosaic of micro‐habitats including physically unstable braided channels and more stable spring‐sources, spring creeks, and groundwater zones. We investigated benthic invertebrate communities at 103 sites in braided channels, springs and hillslope streams in the Waimakariri River, New Zealand over 3 months. One hundred taxa were identified, including a number of rare phreatic species. Highest total taxonomic richness occurred in springs (81 taxa), whereas main braids and hillslope streams had fewer taxa (54 and 56, respectively). Spring‐fed habitats also had the highest diversity of unique taxa (22), whereas main channels had five and hillslope streams 11 taxa, respectively. Several taxa including the mayfly Deleatidium and orthoclad chironomids were ubiquitous, whereas others such as the flatworm Prorhynchus had restricted habitats. Our results highlight the high spatial heterogeneity of braided river habitats and the importance of springs as centres of invertebrate diversity within braided river catchments.